1993
DOI: 10.1128/mcb.13.2.1238
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro analysis of transcriptional activation mediated by the human cytomegalovirus major immediate-early proteins.

Abstract: To define mechanistically how the human cytomegalovirus (HCMV) major immediate-early (IE) Human cytomegalovirus (HCMV), a member of the herpesvirus family, is an important pathogen implicated in a variety of diseases in newborn and immunocompromised individuals (for reviews, see references 2 and 59). Like other members of the herpesvirus family, the genome of HCMV is temporally expressed during the viral life cycle (16, 56,81,88,89 (16,17,29,33,34, 56,64,79,80,82,88,89,91). At least three IE RNAs have been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 92 publications
7
120
0
Order By: Relevance
“…Transient-transfection assays showed that the IE1 and IE2 proteins are potent transcription factors that cooperatively activate transcription from many promoters, including HCMV early promoters (9,21,23). However, these transient-transfection assays do not reflect the actual infection situation.…”
Section: Discussionmentioning
confidence: 99%
“…Transient-transfection assays showed that the IE1 and IE2 proteins are potent transcription factors that cooperatively activate transcription from many promoters, including HCMV early promoters (9,21,23). However, these transient-transfection assays do not reflect the actual infection situation.…”
Section: Discussionmentioning
confidence: 99%
“…pGL2-PVR (2571 bp fragment) promoter luciferase reporter vector and progressive deletions were provided by Dr. G. Bernhardt (Hannover Medical School, Hannover, Germany) (60). pSG5-IE1, pSG5-IE2, and pSG5-IE55 were previously described (24). The IE2 cDNA cloned in the pRSV vector and the zinc finger mutant of IE2, with cysteines 428 and 434 mutated into serine residues (pRSV-IE2-Zn mut), were a gift of Prof. Jay Nelson (61).…”
Section: Plasmids Transfections and Chromatin Immunoprecipitation Amentioning
confidence: 99%
“…These IE2 activities are crucial for transcriptional activation of viral and host genes, as well as for regulation of several cellular functions (19). The IE55 protein is a splice variant of IE2 gene product, with a deletion between residues 365 and 519 in the C terminus, a region required for many IE2 functions, including transcriptional activation and DNA binding (19,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Spi1 cDNA was also PCR amplified and inserted into pGEX2T (Amersham) for use in GST pull down assays (Wara-aswapati et al, 1999). Also for GST pull down assays, hCMV IE1 and IE2 cDNA was previously constructed within pGEX 3X (Klucher et al, 1993). IE2 291-364delA pGEX 2T was PCR amplified using four primers: an internal pair to create a 14 aa deletion 5'ctgcggccatcagagcagcatctccgagttggacaacg3' and 5'cgttgtccaactcggagatgctgctctgatggccgcag3', and external primers: 5'ctcctcggatccagccaccatgggcgcggcgg3', and 5'ctcgaattcctcgtcaatcttgacgcgaccccg3'.…”
Section: Reporter Constructs and Expression Vectorsmentioning
confidence: 99%